Studies of Two Seed-Borne Fungi of Some Malaysian Forest Tree Species - Lee, Su See (1981)
Twenty-six species of saprophytic fungi and ten species of potentially pathogenic fungi were isolated from seeds of five indigenous and three introduced forest tree species. Isolation of the fungi using both the blotter and the agar plate methods was carried out to ensure the isolation of as many species as possible from each seed sample. Six new species of fungi not previously recorded in Malaysia were discovered. They were Beltraniella nilgrica Pirozynski & Patil, Chaetomium trilaterale Chivers, Cylindrocladium scoparium Morgan, Cryptodiaporthe sp., Gliocephalo trichum simplex (J. Meyer) Wiley & Simmons and Gliocladium sp. Various factors affecting the growth of two fungi - Cylindrocladium scoparium Morgan, a new species recorded in Malaysia which is Fotentially pathogenic, and Pestalotiopsis versicol or (Speg.) Steyaert, one of the most commonly occurring saprophytes - were investigated. These factors were the effect of nutrients, light, temperature, pH and various vitamins. Suitable culture conditions were developed for both fungi. Seedling inoculation tests showed that Cylindrocladium scoparium was pathogenic to seedlings of Dipterocarpus grandiflorus Blanco, a species indigenous to Malaysian forests, and Pinus caribaea Mor., a species of tropical pine introduced into and pl anted in this country. An investigation into some of the enzymes produced by the two fungi was also carried out to obtain a better understanding of the roles of C. scoparium and P. versicolor in seed deterioration and pathogenicity.